Nutritional and anti-methanogenic potentials of macroalgae for ruminants - Pandey, Deepak (Burleigh Dodds Series in Agricultural Science, 2021)
The livestock production sector is facing challenges to find alternative feed resources and nutritional strategies to mitigate enteric methane (CH4) emissions from ruminants. Recently, marine macroalgae have emerged as potential anti-methanogenic feed ingredients due to their ability to suppress enteric CH4 production in ruminants. The anti-methanogenic properties of macroalgae have been ascribed to the contents of secondary metabolites, such as halogenated compounds e.g., bromoform in red species, and polyphenols or isoprenoids in brown species. These compounds may suppress methanogenesis by inhibiting the growth and activity of methanogens or by altering rumen fermentation pathways and the patterns of volatile fatty acids production. On the other hand, the anti-methanogenic macroalgae, particularly when added to diets in large amounts, are known to reduce animal performance, due to the presence of special and poorly degradable carbohydrates. Thus, finding a proper balance between the abilities to reduce CH4 emissions and sustain animal performance is important.